Ab initio study of CO adsorption on PdGa(1 1 0) - Bechthold, Pablo Ignacio (2013)
CO adsorption is analyzed using Density Functional Theory (DFT) calculations. Changes in the electronic structure of PdGa(1 1 0) surface and CO bond after adsorption are addressed. CO is located only on Pd atop geometry with a tilted configuration (9.13° from the perpendicular to the surface) and no interaction with Ga is detected. The Pd-Pd bond strength decreases 54.2% as the new Pd-CO bond is formed. The C-O bond length change less than 1%, compared to the gas phase value, while its bond overlap population decrease 46.2%. The effect of CO is limited to its first Pd neighbor. Analysis of orbital interaction reveals the Pd-CO bond mainly involves s-s and s-p orbitals with less participation of Pd 4d orbitals. The computed CO vibration frequencies after adsorption shows a red shift from vacuum to ward 2013.85 cm-1, which agrees with previous experimental data on PdGa intermetallic.